Comparative Study on the Hardness of Mechroha Water Springs (Journal of Engineering, 2022)
The vacancy of natural resources is undoubtedly limited by time. The sustainable development principle recommends modern technology for its protection and renewal. This project conducted analyses on two underground water sources in the north of Algeria (Mechroha Province). Besides, the use of the hardness factor and the adoption of the titration method, which is  the determining the concentration of an unknown solution using a known solution concentration, have permitted the characterization of the examples taken and to verify their conformity to the standard required, the results found showed HT=6.66 French degrees (oF) ) for Ain Guilloume water spring in comparison to Ain Messai water spring HT=7 French degrees (oF). Those data conduct us to select the drinking water source of Ain Guilloume due to its attractive composition and value.